2017
DOI: 10.7759/cureus.1420
|View full text |Cite
|
Sign up to set email alerts
|

Association of Lipid Profile in Pregnancy with Preeclampsia, Gestational Diabetes Mellitus, and Preterm Delivery

Abstract: IntroductionDuring the last two trimesters of pregnancy, glucose is spared (for the foetus), while the concentration of fatty acids in plasma increases, which can create complications like preeclampsia, gestational diabetes mellitus (GDM), and preterm delivery.AimTo study the association of serum lipid levels during the second and third trimesters with the development of pregnancy-associated diseases, such as preeclampsia, GDM, and preterm delivery.Methods and MaterialsThe present study was carried out at MGM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 19 publications
4
26
2
1
Order By: Relevance
“…Previous studies by our team in the same population have demonstrated that: a) WC ≥ 88 cm and pre BMI ≥25 Kg/m 2 have optimal Sens/Sp for predicting GDM at GA <24 weeks 25 ; b) overweight (pre BMI ≥ 25 Kg/m 2 ) and obesity (pre BMI ≥ 30 Kg/m 2 ) are risk factors for hyperglycemia in pregnancy (GDM-MGH) 22 ; and c) the proportion of metabolic syndrome markers is associated with hyperglycemia level in women with GDM-MGH 26 . The results of other studies in diverse populations do not differ from ours 11,13,14,16,42,43 . Also in agreement with other reports, we observed that the higher Sp shown by FG, HbA1c and HOMA-IR indicate them as the best predictors for ruling out GDM risk and the need for a diagnostic test 10,13,42,44,45 .…”
Section: Resultscontrasting
confidence: 66%
“…Previous studies by our team in the same population have demonstrated that: a) WC ≥ 88 cm and pre BMI ≥25 Kg/m 2 have optimal Sens/Sp for predicting GDM at GA <24 weeks 25 ; b) overweight (pre BMI ≥ 25 Kg/m 2 ) and obesity (pre BMI ≥ 30 Kg/m 2 ) are risk factors for hyperglycemia in pregnancy (GDM-MGH) 22 ; and c) the proportion of metabolic syndrome markers is associated with hyperglycemia level in women with GDM-MGH 26 . The results of other studies in diverse populations do not differ from ours 11,13,14,16,42,43 . Also in agreement with other reports, we observed that the higher Sp shown by FG, HbA1c and HOMA-IR indicate them as the best predictors for ruling out GDM risk and the need for a diagnostic test 10,13,42,44,45 .…”
Section: Resultscontrasting
confidence: 66%
“…29 Several studies have found that hypertriglyceridemia, even in early pregnancy, 17 is associated with insulin resistance as well as GDM. [18][19][20][21] Enquobahrie et al found that each 20 mg/dl increase in TG concentration leads to a 10% rise in the risk of GDM. Also, they demonstrated that mothers with TG levels more than 137 mg/dl were 3.5 times more likely to develop GDM.…”
Section: Discussionmentioning
confidence: 99%
“…16 Increasing evidence has suggested that hypertriglyceridemia, even in early pregnancy, 17 is likely to be associated with insulin resistance, 18,19 as well as GDM. 20,21 In addition, fasting plasma glucose (FPG) at the first prenatal visit is related to glycemic metabolism in the mid-gestational period, as suggested in a previous study. 22 Moreover, a recent study has reported that high FPG or BMI in the first trimester of pregnancy is independently associated with later development of GDM.…”
Section: Introductionmentioning
confidence: 87%
“…We found a significant increase in serum concentrations of lipid profile components including TG, total cholesterol, HDL-C and LDL-C from beginning to the late pregnancy in both groups, but the differences were not significant between groups. During pregnancy along with increasing gestational age the levels of lipid profile increase most probably due to hormonal and metabolic changes as a normal physiologic phenomena [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the importance of changes of blood lipid metabolism during pregnancy pertains to its potential effect on perinatal morbidity and mortality. It has been reported that dyslipidemia in pregnancy associated with preeclampsia, GDM, preterm delivery and cardiovascular disease in the future [47]. Based on some evidence, vitamin D deficiency during early pregnancy associated with more unfavorable changes of lipid profile [53,54].…”
Section: Discussionmentioning
confidence: 99%